The importance of professional values from nursing students' perspective - Batool Poorchangizi; Fariba Borhani; Abbas Abbaszadeh; Moghaddameh Mirzaee; Jamileh Farokhzadian (BMC, 2019)
Abstract Background Professional values of nursing students may be changed considerably by curricula. This highlights the importance of the integration of professional values into nursing students' curricula. The present study aimed to investigate the importance of professional values from nursing students' perspective. Methods This cross-sectional study was conducted at the Kerman University of Medical Sciences, Iran. Data were gathered by using a two-section questionnaire consisting of demographic data and Nursing Professional Values Scale-Revised (NPVS-R). By using the stratified random sampling method, 100 nursing students were included in the study. Results Results showed that the mean score of the students' professional values was at high level of importance (101.79 ± 12.42). The most important values identified by the students were "maintaining confidentiality of patients" and "safeguarding patients' right to privacy". The values with less importance to the students were "participating in public policy decisions affecting distribution of resources" and "participating in peer review". The professional value score had a statistically significant relationship with the students' grade point average (P < 0.05). Conclusions In light of the low importance of some values for nursing students, additional strategies may be necessary to comprehensively institutionalize professional values in nursing students.